Pengenalan Media Pemasaran Online Bersama Pemudi pada Usaha Anyaman di Desa Gundik, Slahung, Ponorogo - Hofifah, Siti; Yunita, Ratna (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
Now, information technology is growing rapidly in all fields, including business. Information technology has many benefits, for instance, in marketing activities. Product marketing can utilize information technology such as social media (Instagram) and e-commerce (Shopee). By utilizing social media and e-commerce, the products marketed will be known to the wider community. Marketing is one of the keys to success in maintaining the running of the business and competing with manufacturers of similar products. Woven crafts in Gundik Village, Slahung, Ponorogo are small and medium-sized enterprises. Marketing of these woven craft products is still limited to the surrounding Ponorogo area and is marketed through shops and word of mouth. Therefore, the sales in this business are still small, and many people do not know about this woven craft product yet. Besides, there are many people around this business, for example, the youth community, who have a lot of free time. This community service aims to develop the marketing of the woven craft business and provide knowledge about online marketing media to the youth community so that their daily activities are more productive and they make good use of their free time. The method used in this service was the Asset-based Community Development (ABCD) approach by introducing Instagram social media and e-commerce as product marketing media. As a result, this community service, which focuses on introducing online marketing media to develop the woven craft business and youth community during the introduction process and after the introduction process, has a positive impact.